Relationship Between Group Work Competencies and Satisfaction With Project-Based Learning Among University Students - Melguizo-Garín, Anabel; Ruiz-Rodríguez, Iván; Peláez-Fernández, María Angeles; Salas-Rodríguez, Javier; Serrano-Ibáñez, Elena R. (Frontiers in Psychology, 2022)
There is a growing interest in improving the teaching–learning process at all levels of education, including higher education. In recent years, university institutions have been taking action to renew and modernize the way in which they teach and learn, making the process more dynamic and closer to the current social reality. Competencies such as the ability to work in a team have become essential for the successful implementation of innovative methodologies in which student participation is particularly relevant. Student acceptance is key to the success of any teaching methodology; however, the influence of group work skills on satisfaction with innovative methodologies such as project-based learning (PBL) has not yet been tested among university students. Thus, the objective of this study is to explore the association between group work competencies and satisfaction with PBL. A total sample of 359 students from two Spanish universities participated in the research. Our results reveal that there is a significant and positive relationship between competencies related to group work and satisfaction with PBL. In addition, a multiple regression analysis shows that the competencies “Conception of group work”, “Usefulness of group work”, “Planning of group work by teachers” and “Group norms” increase satisfaction with the use of the PBL methodology. This work expands our knowledge about the role in increasing students’ satisfaction that is played by the ability of college students to work as a team. These findings could also guide teachers interested in new teaching methodologies.